Critical materials determination as a complement to the product recycling desirability model for sustainability in Malaysia - Al Amin, Mohamed Sultan; Wan Mahmood, Wan Hasrulnizzam; Md Saad, Mohd Shamsuri; Qi Hang, Yoong; Mativenga, Paul Tarisai (MDPI AG, 2022)
End-of-life waste disposal is a major issue in Malaysia, where the country’s economy has suffered due to waste recovery issues. Many countries have successfully identified critical materials and products for increasing recycling rates, but not in Malaysia. Thus, the Malaysian government and businesses have had difficulty prioritising products for recycling. The absence of critical materials data has meant that a recovery strategy could not be planned wisely. In addition, the Product Recycling Desirability Model that was utilised by many countries to improve their recycling strategy could not be applied to Malaysia, as it requires critical materials data as input. To start with, Malaysia’s important materials have been identified. Next, two risk dimensions are defined: supply risk and material risk. The indicators are then weighted according to Malaysia’s scenarios. The scores are analyzed and applied to the Product Desirability Model to find desirable products for recycling. As a result, 89 materials were classified as critical to Malaysia’s economy, with palladium, rhodium, gold, platinum, and tellurium ranking first through to fifth. Critical materials scoring was used for the first time in Malaysia to comprehend the Product Recycling Desirability Model, a tool for prioritizing products for recycling. Additional analysis reveals that car batteries, tyres, PET bottles, mobile phones, and DVD-R are the top five most important recyclable products in Malaysia. With the material security database readily available and the novel evaluation system being employed to prioritize critical material supply, using risk supply and material security for Malaysia, the government, or private sector, can strategically start to implement recycling policies and initiatives to strengthen recycling efforts, which help to increase recycling rates.